The promotion of medical policy for the elderly on physical exercise and mental health education for the elderly - Jia Xu; Xiangjun Ren, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
The purpose of the study was to examine the impact of medical policy on physical activity and mental health education in older adults. According to the paper's research objectives and the number of older persons, the elderly over 60 were chosen as survey subjects. The differences and differences in the mental health of the elderly were compared primarily through reverse exclusion and comparison using a questionnaire survey and the SCL-90 symptom self-rating scale. The elderly are found to have a complete understanding of the purpose and value of the physical activity. When they exercise more than three times a week, their maximum oxygen consumption gradually decreases, and the exercise effect is impressive. We should make every effort to address the diverse demands of the elderly aged 70-79 and above. Physical exercise can provide strong support for mental health for the elderly and meet their needs for a healthy and beautiful life, respect and social support. However, due to the lack of overall planning for mental health education, an orderly system has not been formed, which limits the deep-seated pursuit of the elderly in terms of psychological ability improvement, emotional communication and spiritual pension.